Role of Communication in Developing Psychological Contract Breach: Mediating Role of Power Distance - Mallah, Marvi; Syed, Sumaiya; Memon, Salman Bashir (Journal of Economics and Behavioral Studies, 2016)
The communication plays very important role across organizations. Similarly, the psychological contract exists all the time within the organization. This article explains the role of communication in minimizing the psychological contract breach (PCB) mediated by power distance. The organizations are required effective communication in order to create a strong bond between the organization and the employees. The PCB not only has harmful impact on employees but also negatively affect the performance of the organization. This research suggests the impact of communication on PCB if the communication is strong there are more chances of low PCB but if communication is not strong the chances of high PCB within the organization is observed. The research also examines the communication mediated by high and low PD and suggests its impact on the PCB. The research suggest within the organization if communication is strong its leads toward the lower PCB among the employees and when the communication is mediated by lower power distance it will leads toward the lower PCB vis-a-vis.